Providing gender-affirming hormone therapy through primary care: service users - Theresa Fleming; Cathy Stephenson; Antonia Lyons; Gloria Fraser; Alex Ker (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONPrimary health care providers are playing an increasingly important role in providing gender-affirming health care for gender diverse people. This article explores the experiences of a primary care-based pilot clinic providing gender-affirming hormone therapy in Wellington, New Zealand. AIMTo evaluate service users' and health professionals' experiences of a pilot clinic at Mauri Ora (Victoria University of Wellington's Student Health and Counselling Service) that provided gender-affirming hormones through primary care. METHODSIn-depth interviews were conducted with four (out of six) service users and four health professionals about their perspectives on the clinic. Interviews were transcribed verbatim and analysed using thematic analysis. RESULTSThree themes were identified in service users' interviews, who discussed receiving affirming care due to the clinic's accessibility, relationship-centred care and timeliness. Three themes were identified in the health professionals' interviews, who described how the clinic involves partnership, affirms users' gender and agency, and is adaptable to other primary care settings. Both service users and health professionals discussed concerns about the lack of adequate funding for primary care services and the tensions between addressing mental health needs and accessing timely care. DISCUSSIONThe experiences of service users and health professionals confirm the value of providing gender-affirming hormone therapy in primary care. Models based in primary care are likely to increase accessibility, depathologise gender diversity and reduce wait times.